Relation between dietary intake and breast cancer - Hassanein, Manal A. M. (2003)
Nutrition and lifestyle may be largely responsible for the development of common cancer. This research aimed to study the relation-ship between food intake, consumption of specific amino acids and increased risk of cancer. One hundred (100) patients with breast cancer were chosen randomly at the National Cancer Institute Cairo University- Egypt. Data were collected through an interview with breast cancer patients including socia-economics status, 24 hr dietary recall and anthropometric measurements were conducted. Results revealed deficiencies in calcium, vit.A, vit.C and vit.D for women with breast cancer. Results also revealed that the high quality of protein consumed by women with breast cancer was confirmed by calculation of EAAI, B.V. and PER which were higher for age group 25-50 years.
Includes reference.
Summary in Arabic.
1
Keywords: Breast -- Cancer -- Nutritional aspects; Nutritionally induced diseases; Amino acids in nutrition